2012
DOI: 10.1016/j.soncn.2012.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Quality Cancer Care for Family Caregivers

Abstract: Nurses must take a leadership role to provide standards, guidelines, and best practices for support of the caregiver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0
10

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 42 publications
5
114
0
10
Order By: Relevance
“…Na avaliação da QV, o único domínio em que houve variação significativa foi o de vitalidade, com uma queda no índice de 66,3 para 58,9 (T0 para T2) (p < 0,042). Nos demais domínios, os valores no T0 foram similares aos escores observados em outros estudos de metodologia transversal que compararam a QV de cuidadores ou pais de crianças com câncer com cuidadores ou pais de crianças saudáveis 7,8,[22][23][24] . Esses dados sugerem que, já no momento do diagnóstico, existe um impacto nos domínios de QV, e não somente depois de instituído o tratamento, como sugerido por Klassen et al 9 .…”
Section: Resultsunclassified
“…Na avaliação da QV, o único domínio em que houve variação significativa foi o de vitalidade, com uma queda no índice de 66,3 para 58,9 (T0 para T2) (p < 0,042). Nos demais domínios, os valores no T0 foram similares aos escores observados em outros estudos de metodologia transversal que compararam a QV de cuidadores ou pais de crianças com câncer com cuidadores ou pais de crianças saudáveis 7,8,[22][23][24] . Esses dados sugerem que, já no momento do diagnóstico, existe um impacto nos domínios de QV, e não somente depois de instituído o tratamento, como sugerido por Klassen et al 9 .…”
Section: Resultsunclassified
“…Recent reviews of cancer carer studies found that carer interventions tended to address the patient’s care rather than dealing with carers’ unique needs [3,13,27,28]. Based on these findings, several areas were identified as being in need of further research; a) the identification of carers at higher risk of poor outcomes, so that interventions can be targeted to them; b) address socioeconomic differences; c) an economic evaluation, to understand the relationships between intervention delivery costs, health care utilization and intervention effectiveness, and d) the use of innovative technologies to deliver effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…[14,15] As a consequence, family caregivers develop physical and psychological illnesses during caregiving. [6,7,[14][15][16] In addition, they report unmet needs. [16][17][18][19] Background Systematic reviews of qualitative and quantitative literature concerning relatives requirements caring for family members at the end of life care, Funk et al [11] and Stajduhar et al [13] documented that relatives have complex needs different from the people they are caring for, and should be treated as individuals with unique needs.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7,[14][15][16] In addition, they report unmet needs. [16][17][18][19] Background Systematic reviews of qualitative and quantitative literature concerning relatives requirements caring for family members at the end of life care, Funk et al [11] and Stajduhar et al [13] documented that relatives have complex needs different from the people they are caring for, and should be treated as individuals with unique needs. [17][18][19] Frequently caregivers experience giving care as a burden because of the responsibilities involved in helping the patient survive the journey of cancer, or alternatively to have a peaceful death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation